CONTROLLED-RELEASE EFFERVESCENT FLOATING MATRIX TABLETS OF METFORMIN USING COMBINATION OF POLYMERS - Patel, Meenakshi Bhavesh; Shaikh, Farhatjahan; Patel, Vandana; Surti, Naazneen Imtiaz (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: It is always challenging to prepare the floating gastro retentive formulation of the high dose drug. The present research was aimed to prepare gastro retentive controlled release, matrix tablets of metformin, using the combination of different ionic, anionic and polyanionic polymers with HPMC. Methods: Formulations were prepared using sodium alginate, pullulan, kappa carrageenan, xanthan gum, poloxamer 68 in combination with HPMC K15M. All matrix tablets were prepared by direct compression method and evaluated for swelling, floating adhesive period and drug release. Results: All the tablets showed acceptable physicochemical properties. Statistical analyses of data revealed that tablets prepared using HPMC K15M and kappa carrageenan, formulation F2, is best in terms of showing excellent floating properties, extended adhesion periods and sustained drug release characteristics with similarity factor as 92 on comparison with the theoretical release of the drug. Conclusion: The combination of HPMC K15M and kappa carrageenan can be further optimized by applying the appropriate statistical design.